Neoliberalism and media - Phelan S (SAGE Publications Ltd, 2018)
References to neoliberalism are commonplace in media and communication studies. As in other fields, the concept is normally invoked critically; to speak of neoliberalism usually suggests a disposition that is opposed to it. Yet, the concept is not always affirmed as a concept, even by critical scholars. Some interrogate its ready-to-hand authority as a critical keyword (Flew, 2008). Others refer to it with a casual weariness, as if its commonplaceness illustrates its lack of descriptive and explanatory value (Grossberg, 2010). Whatever we make of the concept, it is difficult to talk about the current condition of critical media and communication studies without talking about neoliberalism. If, as Ernesto Laclau (1990) suggests, all identities are structurally constituted by antagonisms, we might call neoliberalism the master antagonist – even more so than capitalism (Garland & Harper, 2012) – of critical research in the field.
Keywords: Political Science; Political economy; Neoliberalism; Media studies; Journalism Studies